Phycocyanin: A Natural Antioxidant to Combat Free Radicals - Zhuang, Dingling; Tang, Doris Y. Y.; Chew, Kit W.; Ling, Tau Chuan (Current Nutrition & Food Science, 2022)
Various research showed that antioxidants can effectively overcome the damage caused by free radicals to human health. Therefore, antioxidants are identified as one of the main directions in the development of health care and cosmetics products due to high demand in the market. This review mainly focuses on the phycocyanin, a type of natural antioxidant mainly found in cyanobacteria. This mini review summarizes the phycocyanin sources and numerous extraction methods of phycocyanin along with the analytical methods and determine its ability to suppress free radicals. Phycocyanin has been proven to play an important role in scavenging free radicals and enhancing the body’s antioxidant capacity. However, there is a lack of long-term randomized clinical trial results that can be used as evidence in showing the benefits of phycocyanin. The existing phycocyanin extraction methods using solvents, ultrasonic-assisted, freeze-thaw, etc. can extract high-quality phycocyanin efficiently and quickly. Scientists are also trying to incorporate advanced technologies, such as
Keywords: supplements